ANALISIS KESALAHAN PENGGUNAAN KATA KETERANGAN “DOU” DAN “QUAN” PADA MAHASISWA ANGKATAN 2014 BAHASA MANDARIN - Evanita Evanita; Ina Ina; Lusi Lusi (Universitas Tanjungpura, 2019)
AbstractGrammar is inseparable from the process of learning language. Grammar is composed of words, sentence components and sentence patterns. Without these ingredients, you can't express what you want to say. Grammar is also one of the difficulties of students in the process of learning Chinese. Adverbs are an important part of the grammar. The most commonly used adverbs are “dou” and “quan”. “Dou” and “quan”are adverbs of scope. They have the same points and differences in semantics. If they are not mastered, students often have errors in their use.The author conducted a survey on the use of the adverbs “dou” and “quan” of Mandarin Education Study Program FKIP UNTAN 2014 students and analyzed the bias of the students. It is concluded that the bias rates for students using “dou” and “quan” are 56% and 53.3%, respectively. According to the bias types “dou” and “quan”, the “missing”is 8% and 13%, “false addition” is 12.2% and 9.5%, and “missing” is 14% and 7%. The wrong order is 9.8% and 16.7%. In addition, it is concluded that the common types of biases are misordered errors and false positives. The reason for the bias is the negative transfer of the mother tongue and the generalization of the target language rules. Keywords: Adverb, Dou and Quan, Analysis